Investigation of Alishahi Village Reconstruction\'s consequences after 2010 Fars Earthquake - Seyyed Amirhossein Garakani; Mohammad Ali Vojdani; Mahsa Bashiri (مسکن و محیط روستا)
In most post-disaster reconstruction programs, relocation of affected settlement is perceived to be an appropriate solution to reduce vulnerability and increase safety to the risk of future hazards. Nonetheless, investigation of various experiences in the country illustrates that outcomes of relocation firmly have not been acceptable for affected people who have been displaced after the disaster. So in some experiences people left the new settlements built by safe technologies in safe places and have come back to old ones despite their vulnerability and probability of hazards in them. In order to explain the necessity of revising the policy of settlements relocation after disasters, the study is taken to indicate in-situ policy for Alishahi Village after Fars Province 2010 Earthquake and to investigate its pros and cones. This is done by using field experiences of authors during the reconstruction procedure, field observations and in-depth interviews with the field study approach and case study method one year after reconstruction time. The policy taken in Alishahi reveals that relocation and resettlement after disasters is not the only choice which is available and by eliminating or reducing vulnerability of the built environment against hazards which may occur in the settlement, in-situ policy may be evaluated as a better option in terms of people’s satisfaction and utilization of existing assets despite higher costs at the beginning of reconstruction. It should be in mind that resistance against hazards cannot be obtained unless accurate observation during reconstruction period. Also in order to have buildings resistant after this period, community capacity has to be elevated by holding educational programs. Beside, while it was thought that the use of indigenous materials and labors and reliance on local knowledge of villagers lead to a slowdown in the reconstruction, in the mentioned experience the reconstruction, compared to the same villages, were done according to the predetermined schedule with the establishment of public participation in the various stages of the housing including planning, deciding and implementation, It also emphasize that designing new houses have to be according to villagers’ needs, demands and nostalgias, so it won’t cause interference in their way of life forming during years and lead to least modifications after reconstruction time.